L3 morphosyntactic processing among Polish–English bilinguals: Considering learners’ level of bilingualism and language dominance - Marciszewska Agnieszka A (De Gruyter, 2021)
Investigating language practices of bilingual children and understanding how they process a novel L3 allow to contribute to epistemological debates on bilingualism. In the present study, Polish–English bilingual children were tested on their processing of subject-first (SVO) and object-first (OVS) sentences in Polish and German. The data collected in this exploratory study were analysed in light of learners’ different levels of bilingualism and language dominance. The results consistently indicate that higher proficiency in Polish as well as ability to process the challenging OVS sentences supports learners in processing L3 German as well. The findings provide useful insights on morphosyntactic processing abilities among both migrant and bilingual 2L1 children and shine light on their needs, which could further be used to inform educational policy in the UK.